Contemporary sample stacking in CE: a sophisticated tool based on simple principles - Malá, Zdena; Krivánková, Ludmila; Gebauer, Petr; Bocek, Petr (Electrophoresis, 2007)
Sample stacking is a general term for methods in CE which are used for on-line concentration of diluted analytes. During the stacking process, analytes present at low concentrations in a long injected sample zone are concentrated into a short zone (stack). The stacked analytes are then separated and individual zones are detected. Thus stacking provides better separation efficiency and detection sensitivity. Many papers have been published on stacking till now, various procedures have been described, and, many names have been proposed for stacking procedures utilizing the same principles. This contribution brings an easy and unified view on stacking, describes the basic principles utilized, makes a list of recognized operational principles and brings an overview of principal current procedures. Further, it surveys selected recent practical applications ordered according to their operational principles and includes the terms, nicknames, and acronyms used for these actual stacking procedures. This contribution may help both newcomers and experts in the field of CE to orient themselves in the already quite complex topic of sample stacking.
Keywords: Sensitivity and Specificity; Electrophoresis, Capillary; koncentrace vodíkových iontů; Hydrogen-Ion Concentration; elektroforéza kapilární; senzitivita a specificita